2013
DOI: 10.1071/he13066
|View full text |Cite
|
Sign up to set email alerts
|

Edible gardens in early childhood education settings in Aotearoa, New Zealand

Abstract: Study findings suggest that gardens are already being used as a versatile teaching tool in many ECES settings. Most gardens are new, with a need to support the sustainability and workforce development among teachers and parents in order to be able to maintain these resources for future generations. SO WHAT?: Given the inherent links between gardening and healthy food and exercise, there seem to be extensive opportunities for health promotion aligned with the edible garden movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Edible gardens were even more widespread, with nine out of ten services growing their own fruit trees and/or vegetables, and most services involving children in gardening activities daily or weekly. This appears to be an increasing prevalence of edible gardens from previous research in 2009 which found 71 % of services in New Zealand grew their own vegetables or had fruit trees (38) . A recent evaluation of funding for edible gardens in child care (39) concluded that these gardens provide opportunities to discuss the importance of fruit and vegetables for health, encourage children to try new foods, provide opportunities for cooking, and have a range of positive outcomes for children and the whole community.…”
Section: Discussionmentioning
confidence: 99%
“…Edible gardens were even more widespread, with nine out of ten services growing their own fruit trees and/or vegetables, and most services involving children in gardening activities daily or weekly. This appears to be an increasing prevalence of edible gardens from previous research in 2009 which found 71 % of services in New Zealand grew their own vegetables or had fruit trees (38) . A recent evaluation of funding for edible gardens in child care (39) concluded that these gardens provide opportunities to discuss the importance of fruit and vegetables for health, encourage children to try new foods, provide opportunities for cooking, and have a range of positive outcomes for children and the whole community.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, our results may not be generalizable to other nurseries in England. However, our response rate is nearly identical to that of a similar survey of 211 ECE programs in New Zealand (54% versus 55%) [56]. Further, we used surveys rather than qualitative interviews or focus groups because we were interested in assessing a wide range of nurseries across England and quantitatively exploring associations rather than the range of perceptions present.…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of community gardens and other urban open spaces have encouraged many governments to plan specific spaces for food planting [39,40]. Edible parks, community farms, school gardens, and rooftop gardens are the main growing areas in most countries [9,23,24]. In China, there were no public spaces planned for agriculture use in urban areas.…”
Section: Significance Of Government's Plan and Managementmentioning
confidence: 99%
“…In most developed countries, edible elements such as vegetables, fruits, and herbs were introduced into community gardens, school gardens, and home gardens [4,6,43,45,54]. This mainly provided the social benefit of natural education for the public [3,23,24], which attracts most urban residents' participation [37,43]. Compared with developed countries, most developing countries such as Argentina, Brazil, and Nepal implemented edible landscape projects to provide high-quality food supply [3,16,36].…”
Section: Limitations and Prospectsmentioning
confidence: 99%